Knockdown of PHF5A Inhibits Migration and Invasion of HCC Cells via Downregulating NF-κB Signaling. (15th January 2019) - Yang, Qing; Zhang, Jianwen; Xu, Shilei; Jia, Changchang; Meng, Wei; Tang, Hui; Zhang, Xiaomei; Zhang, Yi; Fu, Binsheng
Abstract : Background. Inflammation is the major risk factor for the progression of hepatocellular carcinoma (HCC), and the nuclear factor- κ B (NF- κ B) signaling plays the central role in the inflammation process. However, the activated mechanism of NF- κ B signaling in HCC is unclear. Methods. The expression of PHF5A is examined by qPCR, western blotting, and immunohistochemistry (IHC) assay. The potential of PHF5A (PHD-finger domain protein 5a) for migration and invasion is examined by wound healing and Transwell assay. Luciferase reporter assay, western blotting, and qPCR were applied to explore the mechanism by which PHF5A is involved in progression of HCC. Results. PHF5A was significantly upregulated in HCC tissues and cells. Downregulation of PHF5A inhibits the migration and invasion of HCC cells. Further study demonstrated that PHF5A is implicated in HCC progression through NF- κ B signaling. In addition, blocking the NF- κ B signaling can weaken the stimulatory effect of PHF5A on migration and invasion of HCC cells. Conclusion. PHF5A expression is upregulated in HCC tissues, and depletion of PHF5A inhibits the migration and invasion of HCC cells. Further experiments demonstrated that PHF5A is implicated in NF- κ B signaling and knockdown of PHF5A downregulates the activity of NF- κ B pathway to inhibit the tumor progression. The above results provide the evidence that PHF5A plays an indispensable role in progressive effect of NF- κ B pathway in HCC and may be a novel therapeutic target of HCC.